Nonequilibrium plasma aerotaxy of size controlled GaN nanocrystals. (18th December 2019) - Uner, Necip B; Thimsen, Elijah
Abstract: High quality gallium nitride (GaN) nanocrystals (NCs) are promising materials in a wide range of applications including optoelectronics, photonics and biomedical devices. Unlike II–VI semiconductors, the synthesis of free-standing GaN NCs is not well-established, and there is a need for a synthesis platform that can provide GaN NCs with tunable size and photonic properties. In this work, we present a flexible gas-phase synthesis method that can deliver crystalline, free-standing, pure GaN NCs with controlled size and narrow size distributions. The method, termed nonequilibrium plasma aerotaxy (NPA), employs an aerosol of Ga and gaseous N2 as the precursors. The term aerotaxy means growth on an unsupported surface, in this case promoted by a nonequilibrium plasma. The key to narrow size distributions is that the NPA mechanism is based upon surface growth, as opposed to coagulation mechanisms that result in broad size distributions. The NPA process converts the Ga aerosol into GaN NCs within 10–100 ms of residence time. The mechanism involves non-thermal vaporization of the source Ga aerosol, which is followed by nucleation and reaction with the excited N2 species in the plasma. Particles can be made to be either hollow or solid. Solid NCs were found to be photoluminescent. Large NCs emitted photons at a peak wavelength near the bulk band-gap transition. Tuning the size to be smaller than 7 nm average diameter led to a blue-shifted photoluminescence. Inline processing of these bare GaN NCs into porous films by supersonic impact deposition is demonstrated. Moving beyond the specific example of GaN, the NPA mechanism is general and can be extended to many other binary, ternary or doped semiconductors.